The Effect of Masonry Cracks on the Composite Action Between Steel Lintels and Masonry Walls - Hardy, S.J. (Engineering Transactions, 1995)
The paper discusses results of an analytical investigation into the effect of horizontal and vertical masonry cracks on the composite action between that masonry and the supporting steel lintel. The results confirm previous experimental data which suggest that the effect of any discontinuity in the masonry is highly position-dependent. Vertical cracks are shown to be particularly damaging. In addition, experimental tests are described which investigate the influence of the level of friction bonding at the lintel/masonry interface on the resulting structural behaviour.